The impact of digital transformation on strategic management in the digital age: meta-analysis - Angula, Nikodemus; Asa, Asa Romeo (BOHR International Journal of Advances in Management Research, 2025)
Digital transformation (DT) is one of the central aspects shaping the fundamentals of strategic management in a world of persistent and rapid digital change. This meta-analysis study analyzed data from various empirical studies to explore the implications of DT on strategic management processes across a number of industries. By reviewing the empirical research on DT from the last two decades, we find many implications of DT technologies such as big data analytics, artificial intelligence (AI), cloud computing, and digital platforms for strategic decision-making, organizational agility, organizational innovation, and competitive advantage. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) to collect and synthesize information from databases (Scopus, Web of Science, Google Scholar, and EBSCO), we provide systematic analysis for sources published from 2017 to 2024. The results gathered show that incorporating traditional technological forces such as AI, big data analytics (BDA), cloud computing, blockchain, and Internet of Things (IoT) is a feature of the digital era. Participants from the different studies we reviewed stated that the result of DT has changed the way organizations operate, especially for strategic decision-making.